2024
DOI: 10.1039/d3fo04334g
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb2 exhibits therapeutic value for male osteoporosis in orchiectomy mice by suppressing osteoclastogenesis and modulating NF-κB/MAPK signaling pathways

Yanhuai Ma,
Jianliang Li,
Jiale Mai
et al.

Abstract: Osteoporosis (OP), is a systemic disorder characterized by decreased bone mass as well as deteriorated microarchitecture. Although OP in men is common, it receives much less attention than in women.Ginseng,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(71 reference statements)
1
0
0
Order By: Relevance
“…We found that the oral administration of TS had the best inhibitory effect on NF-κB and MAPK signaling pathway activation among three different administrations of SC-5, TY, and TS. These data suggest that the ameliorating effect of TS on colonic inflammation in mice is related to the inhibition of NF-κB and MAPK pathways, this is consistent with the findings of previous studies [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 93%
“…We found that the oral administration of TS had the best inhibitory effect on NF-κB and MAPK signaling pathway activation among three different administrations of SC-5, TY, and TS. These data suggest that the ameliorating effect of TS on colonic inflammation in mice is related to the inhibition of NF-κB and MAPK pathways, this is consistent with the findings of previous studies [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 93%